Clearance of HR-HPV within one year after focused ultrasound or loop electrosurgical excision procedure in patients with HSIL under 30. (1st January 2022) - Qin, Yi; Li, Qing; Ke, Xunyu; Zhang, Yan; Shen, Xiaoling; Wang, Wenping; Shi, Qiuling; Li, Chengzhi
Abstract: Objective: To compare the clearance rate of high-risk human papillomavirus (HR-HPV) in patients with a high-grade squamous intraepithelial lesion (HSIL) 12 months after focused ultrasound (FUS) or loop electrosurgical excision procedure (LEEP), and analyze the influencing factors. Methods: A retrospective cohort was established in HSIL patients with HR-HPV infection treated with FUS or LEEP from 2015 to 2019. The cohort consisted of 321 patients under 30 years of age, of which 119 patients received FUS and 202 patients received LEEP. The Cox regression model was used to identify the influencing factors for HR-HPV clearance. Kaplan–Meier method was applied to estimate the efficacy of FUS and LEEP in HR-HPV clearance, and the log-rank test was used to compare the efficacy difference between FUS and LEEP. Results: Multivariate Cox regression analysis showed that both FUS and LEEP were independent influencing factors for HR-HPV clearance. HR-HPV cleared faster in the FUS group than in the LEEP group [the median time to HR-HPV clearance: 6 months in the FUS group (95% CI: 5.492–6.508) and 6 months in the LEEP group (95% CI: 5.734–6.266), p = 0.021]. The HR-HPV clearance rates at 6 and 12 months were 54.6% and 94.1% respectively in the FUS group, and 50.5% and 79. 2%, respectively in the LEEP group ( p = 0.001 at 6 months, p = 0.000 at 12 months). Conclusions: For HPV-positive HSIL patients under 30, FUS had a better HR-HPV clearance effect than LEEP 1 year after treatment. FUS may be a viable modality for the treatment of young HSIL patients.